Analysis of Groundsill Design in Cimanuk River, Jatitujuh, Majalengka - Septian Awaludin; Lukman Dulhaki; Nurdiyanto (Riviera Publishing, 2025)
This study analyzes the groundsill design in the Cimanuk River at the Jatitujuh area, Majalengka, with the goal of addressing riverbed degradation and enhancing flood control. The research aims to provide a sustainable solution by stabilizing the riverbed and preventing further erosion, which threatens the river’s hydraulic structures. The study utilizes a combination of hydrological analysis, including discharge frequency analysis, and morphological analysis to calculate the design of the groundsill structure. The hydrological analysis employs several methods, with the Log Pearson III method identified as the most suitable for calculating the 100-year return period flood discharge of 1,444.28 m³/s. The structure’s design includes a main dam height of 3.83 meters and a sub-dam height of 1.10 meters, with stability analysis confirming its safety against overturning and shear forces. The findings indicate that the groundsill will reduce water velocity, prevent further riverbed degradation, and maintain the structural integrity of the Rentang Weir. The study highlights the need for community participation in maintaining the groundsill and calls for further environmental impact assessments and climate change considerations. This research contributes to the development of effective river management strategies and provides recommendations for future studies, including optimization of the groundsill design under varying conditions and exploring the effects of climate change on river discharge.